4-level capacitor-clamped boost converter with hard-switching and soft-switching implementations - A.N. Kasiran; Asmarashid Ponniran; A.A. Bakar; M.H. Yatim (Institute of Advanced Engineering and Science, 2019)
This paper presents parameters analysis of 4-level capacitor-clamped boost converter with hard-switching and soft-switching implementation. Principally, by considering the selected circuit structure of the 4-level capacitor-clamped boost converter and appropriate pulse width modulation (PWM) switching strategy, the overall converter volume able to be reduced. Specifically, phase-shifted of 120° of each switching signal is applied in the 4-level capacitor-clamped boost converter in order to increase the inductor current ripple frequency, thus the charging and discharging times of the inductor is reduced. Besides, volume of converters is greatly reduced if very high switching frequency is considered. However, it causes increasing of semiconductor losses and consequently the converter efficiency is affected. The results show that the efficiency of 2-level conventional boost converter and 4-level capacitor-clamped boost converter are 98.59% and 97.67%, respectively in hard-switching technique, and 99.31% and 98.15%, respectively in soft-switching technique. Therefore, by applying soft-switching technique, switching loss of the semiconductor devices is greatly minimized although high switching frequency is applied. In this study, passive lossless snubber circuit is selected for the soft-switching implementation in the 4-level capacitor-clamped boost converter. Based on the simulation results, the switching loss is approximately eliminated by applying soft-switching technique compared to the hard-switching technique implementation.